Quality of life and clinical correlates in cognitively-able autistic adults: A special focus on sensory characteristics and perceived parental support - Chun-Yi Lin; Yi-Lun Wu; Yi-Ling Chien; Susan Shur-Fen Gau (Journal of the Formosan Medical Association)
Background: Quality of life (QoL) has been suggested as an indicator of outcomes in autistic adults. Factors associated with QoL in autistic individuals remain unclear. This study aims to examine the subjective QoL for autistic adults in Taiwan and investigate the determinants for different domains of QoL. Methods: The study comprised 90 autistic adults (aged 26.9, SD 7.3; males, 80.9%). We used Taiwanese version of World Health Organization Quality of Life-BREF to measure QoL. Four domains of QoL were compared with 61 non-autistic controls, including physical, psychological, social, and environment. To identify the correlates of QoL domains, we assessed IQ, personality trait, family support, anxiety/depressive symptoms, autistic severity, and sensory symptoms by various questionnaires, and assessed their association with QoL by correlation analyses and model selection. Results: Our results showed that autistic adults reported lower QoL on the World Health Organization Quality of Life (WHOQOL)-BREF across all domains. QoL was significantly associated with autistic symptom severity, harm avoidance, family support, sensory symptoms, anxiety, and depression, but not intelligence. Model selections revealed male sex, poor paternal support, autism severity, depression, anxiety, and sensory symptoms were associated with specific QoL domains. Conclusion: Findings supported lower QoL in autistic adults. Modifying the QoL correlates may improve life quality in autistic adults. Furthermore, our findings revealed the importance of sensory symptoms and paternal support in QoL of autistic adults, which was a novel finding in this population.